External quality assurance program for diagnostic complement laboratories: evaluation of the results of the past seven years - Kirschfink, Michael; Frazer-Abel, Ashley; Balogh, Emese; Goseberg, Sabine; Weiss, Nathalie; Prohászka, Zoltán (Frontiers in Immunology, 2024)
The complement external quality assurance (EQA) program was first organized in 2010 by a group of researchers working in diagnostic complement laboratories.Starting in 2016, INSTAND eV, a German, non-profit interdisciplinary scientific medical society dedicated to providing expert EQA programs for medical laboratories, started organizing the EQAs for complement diagnostic laboratories together with the same group of experienced scientists and doctors who also work as EQA experts.The aim of the current work is to provide descriptive analysis of the past seven years' complement EQA results and evaluate timeline changes in proficiency testing.Methods: Each year, in March and October, blinded samples (normal, pathological) were sent to the participating diagnostic laboratories, where complement parameters were evaluated exactly as in daily routine samples. Since no reference method/target values exist for these parameters, and participants used different units for measurement, the reported results were compared to the stable mean (Algorithm A) of the participants using the same method/measurement units. A reported result was qualified as "passed" if it fell into the 30-50% evaluation/target range around the mean of reported results (depending on the given parameter).Results: While the number of participating laboratories has increased in the past years (from around 120 to 370), the number of complement laboratories providing multiple determinations remained mostly unchanged (around 30 worldwide). C3, C4, C1-inhibitor antigen and activity determinations provided the best proficiency results, with >90% passing quotas in the past years, independent of the applied method.Determination of the functional activity of the three activation pathways was good in general, but results showed large variance, especially with the pathological samples.Complement factor C1q and regulators FH and FI are determined by only a few laboratories, with variable outcomes (in general in the 85-90% pass range).Activation products sC5b-9 and Bb were determined in 30 and 10 laboratories, respectively, with typical passing quotas in the 70-90% range, without a clear tendency over the past years.With these accumulated data from the past seven years, it is now possible to assess sample-, method-, and evaluation related aspects to further improve proficiency testing and protocolize diagnostic complement determinations.